First evidence of insecticidal potential of molecules produced during the parasitic phase of the endoparasitoid Cotesia flavipes - Pinto, Ciro Pedro Guidotti [UNESP]; dos Santos, Josy Aparecida; Silva, Felipe Alexsander Rodrigues [UNESP]; Balbuena, Tiago Santana [UNESP]; Rossi, Guilherme Duarte [UNESP] (Wiley, 2022)
Immature endoparasitoids develop inside their hosts. Consequently, endoparasitoids need to circumvent the action of the immune system and reprogram the physiology of their hosts to develop successfully. For this, parasitoids release host regulation-related molecules into their host’s hemolymph produced by the parasitoid itself or expressed in specific host cells infected by parasitoid symbiotic viruses. In addition to their roles in host regulation, these molecules may also present biotechnological potentials, such as for insecticidal purposes in crop protection. We performed a survey for the biotechnological potential of compounds present in the hemolymph serum with and without circulating cell contents of Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae) parasitized by Cotesia flavipes Cameron (Hymenoptera: Braconidae) as insecticides in feeding assays. Hemolymph serum from D. saccharalis larvae at 6 days after the start of the parasitism with and without circulating cell contents were collected and spread over artificial diet or over sugarcane leaves for feeding assays with D. saccharalis neonates. Hemolymph serum with or without circulating cell contents from non-parasitized D. saccharalis larvae at the same age were used as controls. Subsequently, hemolymph serum plus circulating cell contents was fractioned using molecular filters and fractions with different molecular weight range were used for feeding assays with D. saccharalis neonates. Feeding larvae with leaf disks amended with hemolymph serum plus circulating cell contents from parasitized hosts resulted in an increase of ca. 30% in the mortality of D. saccharalis neonates. After fractioning hemolymph serum plus circulating cell contents, feeding assays with the >100 or 3–10 kDa fractions did not result in the previously observed increase in larval mortality, but resulted in a reduction of leaf consumption by neonates. Finally, we selected a parasitism-specific protein band observed in the hemolymph >100 kDa fraction for mass spectrometry identification. This parasitism-specific protein was similar to hymenopteran apolipophorins-I. We conclude that there is an insecticidal potential in the hemolymph serum plus circulating cell contents of D. saccharalis larvae parasitized by C. flavipes and further investigations will be performed to identify, characterize, and uncover the biotechnological application of these molecules.